Corporate Responsibility As A Legal Subject For Song Copyright Infringement - Ismaidar Ismaidar; T. Riza Zarzani; Rahmah Hayati Sinaga (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
Corporate crime is one of the activities or activities that arise in line with rapid developments in the economic and technological fields. The development of the position of corporations as business institutions is increasingly strengthening, making corporations as legal subjects dominate economic life without government control. One of the corporate violations that frequently occurs today is song copyright infringement. Violations that have a major impact on the music business, especially on songwriters as owners of original works . The law that regulates copyright infringement is Law Number 28 of 2014 concerning Copyright. Copyright is an exclusive right for the creator or recipient of the right to publish or reproduce his creation or work by giving permission to do so without prejudice to restrictions according to applicable laws and regulations. The method used in this research is a normative legal research method which examines laws and regulations in a society's legal system relating to corporate responsibility as a legal subject for violations of song copyright . The data collection method is qualitative descriptive analysis with emphasis on literature study. The aim of this research is to determine the factors that cause corporations as legal subjects to violate song copyright and the responsibility of corporations as legal subjects to violate song copyright.